Interconnectedness in all directions – experiences with network structures in supporting refugees in training - Benneker, Gerburg [Verfasser]; Heinzelmann, Susanne [Verfasser]; Lenz, Julian [Verfasser] (My University, 2024)
"Refugees require extensive assistance in many areas of life, especially at the transition to training. Coordination of support provision is, however, a challenge. The results of the evaluation of the “Career Orientation for Immigrants (BOF)” Programme show how important a broad networking of project providers is in order to support immigrants in training. The article formulates recommendations in this regard." (authors' abstract; BIBB-Doku)
Keywords: P 1.5 Migranten; L 5 Beratung & Orientierung; 370; Flüchtling; Bildungsbegleitung; Vernetzung; Berufsorientierung; Programm; Evaluation